Australian Law to Combat Illegal Logging in Indonesia: A Gossamer Chain for Transnational Enforcement of Environmental Law. Issue 2 (July 2017) - Rose, Gregory
Abstract : Two countries' combined crime‐fighting ability might be greater than the sum of their individual capacities where their capabilities complement each other. This article investigates transnational coordination against environmental crime. Australian utilization of mutual legal assistance and anti‐money laundering mechanisms to prosecute offences related to illegal logging in Indonesia are examined as a case study. In theory, interrupting the transfer of proceeds of environmental crime across national borders enhances transnational law enforcement. The case study demonstrates that difficult legal obstacles can obstruct practical cooperation between neighbouring countries combating transnational environmental crime in the timber sector. Therefore, international harmonization of environmental crime laws is needed.